Long term follow-up report of cardiac toxicity in patients with multiple myeloma treated with tandem autologous hematopoietic stem cell transplantation - Koželj, Mirta (Radiology and oncology (Ljubljana), 2013)
Background. Tandem autologous hematopoietic stem cell transplantation (ta-HSCT) is a standard treatment for multiple myeloma (MM). Patients receive a high-dose cyclophosphamide (CY), followed by two myeloablative cycles of melphalan (MEL). There are scarce data about long term cardiotoxicity. Patients and methods. We studied 12 patients (62.25 8.55 years) six years after the completion of MM treatment with ta-HCST. Late cardiotoxic effects were evaluated clinically and echocardiographically. Results. None of the patients developed clinical signs of heart failure, all were in sinus rhythm and NT-pro BNP concentration was elevated (778 902.76 pg/mL). The left ventricular (LV) size remained normal. The LV ejection fraction did not decrease (73.75 5.67%, 69.27 6.13%, p = NS). The LV diastolic function parameters (E, A, ratio E/A and A/a) did not change significantly. In tissue Doppler parameters we observed a nonsignificant decrease in Em (10.26 2.63 cm/s, 7.57 1.43 cm/s) and Sm velocities (8.7 0.87 cm/s, 7.14 1.17 cm/s, p = NS). The E/Em values were in an abnormal range (8.66 1.05, 10.55 2.03). Conclusions. The treatment of MM with ta-HSCT, during which patients receive a high dose CY followed by two myeloablative cycles of MEL, causes mild, chronic, partially reversible and clinically silent cardiotoxic side-effects. However, ta-HSCT in patients with MM is a safe regarding cardiotoxic side effects, but, because of increasing life expectancy needs long term attention.
Keywords: cardiotoxicity; cyclophosphamide; echocardiography; kardiotoksičnost; melphalan; myeloma; plazmocitom; presaditev krvotvornih matičnih celic; therapy; zdravljenje